1978
DOI: 10.1111/j.1751-0813.1978.tb02464.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Distribution of Leptospiral Titres in Cattle and Pigs in Queensland

Abstract: Serological test results for leptospiral species on serums from cattle and pigs performed by the diagnostic laboratories of the Queensland Department of Primary Industries from July 1973 to June 1976 were used to determine the prevalence and geographical distribution of 3 leptospiral serotypes in Queensland. There was a higher prevalence of antibodies to L. hardjo than to L. pomona in cattle, whereas in pigs the prevalence of antibodies to L. pomona was much higher than that for L. tarassovi or L. hardjo. Fera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Leptospira species has previously been detected in feral pigs caught on piggeries in Queensland at a prevalence of 31 per cent (Elder and Ward 1978). During the time of the Elder and Ward (1978) study, 1972–1976, piggeries were more of a sideline enterprise, and were generally free-range in style, so would have been more accessible to feral pigs than they are now (Richardson and O'Connor 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptospira species has previously been detected in feral pigs caught on piggeries in Queensland at a prevalence of 31 per cent (Elder and Ward 1978). During the time of the Elder and Ward (1978) study, 1972–1976, piggeries were more of a sideline enterprise, and were generally free-range in style, so would have been more accessible to feral pigs than they are now (Richardson and O'Connor 1978).…”
Section: Discussionmentioning
confidence: 99%
“…During the time of the Elder and Ward (1978) study, 1972–1976, piggeries were more of a sideline enterprise, and were generally free-range in style, so would have been more accessible to feral pigs than they are now (Richardson and O'Connor 1978). The prevalence of Leptospira species in feral pigs has increased since the time of the Elder and Ward (1978) study, despite the incorporation of a vaccination routine on piggeries for L interrogans serotype Pomona. This indicates that feral pigs are a stand-alone reservoir of Leptospira species infection, and pose a source of infection for domestic pigs in the absence of protective vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…The different geographical distribution of L . pomona and L. h a r d j o prevalences (Elder and Ward 1978) and beef and dairy cattle populations (Anon 1983) may also have influenced the observed differences.…”
Section: Type O F Stock Differencesmentioning
confidence: 96%
“…Therefore, the routine diagnosis of leptospiral abortion largely depends on serological examination of the herd. Interpretation of serological tests is made difficult by a high prevalence of infection in cattle (Elder and Ward 1978), by the persistence of leptospiral titres in cattle for years following infection and by the common practice of bleeding cattle only once, at variable times, after abortion has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of 1485 beef herds in Queensland showed that Leptospira inferrogans serovar hardjo (hereinafter referred to as L. hardjo) antibodies were present in 62% of herds (Elder and Ward 1978). O n Swan's Lagoon Cattle Field Research Station, L .…”
Section: Introductionmentioning
confidence: 99%